2019
DOI: 10.1097/md.0000000000016131
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the rs7101 and rs1063169 polymorphisms in the FOS noncoding region and susceptibility to and prognosis of colorectal cancer

Abstract: Background: The FOS gene is located on human chromosome 14q21–31 and encodes the nuclear oncoprotein c-Fos. This study analyzed the correlation between the FOS noncoding region rs7101 and rs1063169 polymorphisms and colorectal cancer susceptibility and prognosis. Methods: We analyzed the FOS genotypes in 432 colorectal cancer patients and 315 healthy subjects by PCR/Sanger sequencing. Survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…54 Interestingly, we identified associations between mutation of FOS, DOT1L, and VEGFA and metastasis-negative lymph nodes in ESCC. The mutation of FOS is reportedly associated with poor prognosis in colorectal cancer, 55 and high expression of DOT1L and VEGFA indicates poor prognosis in many cancers, such as lung cancer, gastric cancer, and clear cell renal cell carcinoma. [56][57][58][59] These reports imply that mutation of these genes is potentially associated with the Figure 6 The correlation between metastatic lymph node status and the prognosis of ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…54 Interestingly, we identified associations between mutation of FOS, DOT1L, and VEGFA and metastasis-negative lymph nodes in ESCC. The mutation of FOS is reportedly associated with poor prognosis in colorectal cancer, 55 and high expression of DOT1L and VEGFA indicates poor prognosis in many cancers, such as lung cancer, gastric cancer, and clear cell renal cell carcinoma. [56][57][58][59] These reports imply that mutation of these genes is potentially associated with the Figure 6 The correlation between metastatic lymph node status and the prognosis of ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of the currently identified leader genes, reported in Table 2 , revealed their involvement in several biological processes, such as cell signaling (i.e., CTNNB1, CBL, GRB2, PIK3CA, PIK3R1), transcriptional pathways (i.e., JUN, RELA), cell proliferation/differentiation (i.e., FOS) and immuno-inflammatory processes (i.e., IL1B, IL4, IL6, IL10; see Table 2 ) [ 22 ]. Evidence supporting the role exerted by leader genes in both CRC and periodontitis pathogenesis [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], reported in Table 2 , suggested that the pathogenic mechanisms underlying the association between periodontitis and CRC may be mainly related to the effect of the products of the leader genes on cell cycle dysregulation and on alteration of the immuno-inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Leader genes acting in cell cycle regulation, such as CTNNB1, FOS, JUN, GRB2, PIK3CA, and PIK3R1, may affect homeostasis in both colonic cells and periodontal tissues, causing, if dysregulated, colonic cell proliferation and malignant transformation, on the one hand, and periodontitis development and progression, on the other, as described in Table 2 [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations